(untitled) - Rond, Mark de (Cambridge, 2003)
Strategic alliances are generally analyzed as planned and rational developments with clearly measurable outcomes in traditional management textbooks. Mark de Rond argues that such a view is unrealistic. Instead, he emphasizes the social dimension and the importance of the individuals involved inside alliances. Based on in-depth case studies of three major biotechnology alliances, the book combines insights from social theory and intellectual history with more mainstream strategic management literature. It provides a thought-provoking analysis that appeals to the reflective professional as well as academic researchers.
Keywords: Strategic alliances (Business),Liên minh chiến lược (Kinh doanh)